Ultrasound-guided endoscopy to improve accuracy of persistent urogenital sinus (PUGS) diagnosis in adult patient: A case report - Mirandola, Mariateresa; Gui, Benedetta; Naldini, Angelica; Foschi, Nazario; Casula, Viola; Testa, Antonia Carla; Scambia, Giovanni; Catena, Ursula (Frontiers in Surgery, 2023)
Introduction: persistent urogenital sinus (PUGS) is a rare condition characterized by abnormal communication between the urethra and vagina, that can frequently be associated with other complex Mullerian malformation (33%)1-5. We present a case of PUGS associated with a complex Mullerian malformation diagnosed in adult age after the integration of gynecological ultrasound with hysteroscopy, both performed by expert operators. Case description: 27-year-old women was referred to our clinic because of frequent urinary tract infections and cyclic pelvic pain. She was virgo, with normal menstrual cycles and dysmenorrhea. A didelphys uterus and double vagina with bilateral hematocolpos was firstly diagnosed through transrectal and transabdominal ultrasound. An MRI was then performed and a monorenal and ipsilateral ureteral malformation were diagnosed; in addition, a complete absence of the lower third of the vagina and an abnormal origin of the urethra from the bladder were described. Patient underwent lower genital tract endoscopy: external vaginal orifice was obliterated, a PUGS was diagnosed and both vaginas’ ostia were detected on the PUGS’s posterior-lateral walls. The procedure was performed under transabdominal ultrasound guidance which confirmed the endoscopic anatomical suspicion, avoiding complications such as perforation and misdiagnosis. Discussion: ultrasound guided endoscopy plays an essential role in the evaluation of complex anatomic anomalies, such as persistent urogenital sinus (PUGS), leading to a dynamic one-stop diagnosis1; it avoids delays and misdiagnosis in preoperative assessment possibly related to the separately application of different radiological and endoscopic techniques.